Insulin-Like Growth Factor Axis Expression in Dental Pulp Cells Derived From Carious Teeth - Alkharobi, Hanaa Esa; Al-Khafaji, Hasanain; Beattie, James; Devine, Deirdre Ann; El-Gendy, Reem (Frontiers in Bioengineering and Biotechnology, 2018)
The insulin-like growth factor (IGF) axis plays an important role in dental tissue regeneration and most components of this axis are expressed in human dental pulp cells (DPCs). In our previous study we analysed IGF axis gene expression in DPCs and demonstrated a novel role of IGFBP-2 and -3 in coordinating mineralised matrix formation in differentiating DPCs. A more recent study from our laboratory partially characterised dental pulp stem cells from teeth with superficial caries (cDPCs) and showed that their potential to differentiate to odontoblasts and or osteoblasts is enhanced by exposure to the mild inflammatory conditions characteristic of superficial caries. In the present study we examine whether changes apparent in IGF axis expression during osteogenic differentiation of healthy DPCs are also apparent in DPCs derived from carious affected teeth.